Characteristics of Land Resources as Foundation of Watershed Management in Sub Watershed Merawu, Serayu - Beny Harjadi (Universitas Muhammadiyah Surakarta, 2004)
In 2000, the area of DAS critical land in Indonesia is approximately 23,242,881 ha which consists of forest area 8,136,646 ha (35%) and non forest area 15,106,234 ha (65%). In the contrary, the fact shows that in 1989/ 1990 (the beginning of ‘Pelita’/ the five years development planning owned by the government), the area of DAS critical land in Indonesia was 13,180,000 ha only that consists of forest area 5,910,000 ha and non forest area 7,270,000 ha. The cause and its location of negative improvement of the above DAS has not been predited yet. The one of the causes is the weakness of information system on very DAS management system in the aspect of biophysical, soial, eonomical, and cultural. Therefore, it needs the improvement of DAS management which is supported by the result of research and development. The purpose of this research is to get the potency information and the possibility of sensitivity of the land resources in the frame of DAS management with biophisical land as the parameter. Sub DAS of Merawu (21,860 Ha) isas one of the parts of ‘bulu’ DAS Serayu with stream flow minimum 0,81 m3/second and maximum 108 m3/second. The sub DAS of Merawu as the part of ‘bulu’ Serayu has the type of climate A and B with annual rainfall approximatelly 2,000 mm and it can support everything in the stream flow of in order to prevent the flood. This ondition is caused by the permanent vegetation such as forest, underbrsuh or srub, tea garden, as well as multi – plantgarden that has around 40% happen in the ineptisol land, although precipitous slope and very precipitous (25%). The technique of land conversation is good enough in its development, mainly in the dry section of the field by using ‘teras gundul’ and ‘teras bangku’ the society near Sub DAS of Merawu is densely populated, its is around 517 up to 827 persons/ square with their main profession as farmer and their income is around Rp 2.000.000 per year. Bya analysing the above DAS management, it an show that sub DAS of Merawu has the potency of water both for internal and external DAS consuming. The potency of using the land for farimng one season in length (class II, III, and IV) consists of around 50,8%. The development multy plant garden (25% area of DAS) is as the type of potential farming effort because of the diversity of both the result and time; besides it is also as the form of protection toward the effetive land. The possibility of sensitivity is too wide land which is susceptible toward the slide (land slide), mainly in the middle part of the DAS. The live dependee of land which strong enough is as the threat toward the future resoures conservation.